أهمية وموقع النفط في الاقتصاد الأمريكي - قنوع نزار; سطايحي هيثم; صيوح لؤي (Latakia University Journal - Economic and Legal Sciences Series, 2019)
يعتبر النفط من أهم مصادر الطاقة في العالم عامة والاقتصاد الأمريكي خاصة لتمتعه بأفضل الخصائص الفيزيائية بين جميع مصادر الطاقة. وكون النفط من الناحية العلمية والعملية متفوقاً على جميع مصادر الطاقة برزت أهميته كداعم أساسي للاقتصاد. وتعتبر الولايات المتحدة الأمريكية من أكبر الدول المنتجة والمستهلكة للنفط في العالم, فهو من الموارد التي تثير اهتمامها ويدفعها لاستخدام الوعود تارة والتهديدات تارة أخرى من أجل استمرار سيطرتها على احتياطياته العالمية ووسائل نقله، وبناءً على ما تقدم تناول البحث أهم الأفكار التي تخدم الموضوع وفقاً لما يأتي: 1ـ الاقتصاد الأمريكي 2ـ أهمية النفط في الاقتصاد الأمريكي. 3ـ أسباب هبوط احتياط النفط الأمريكي. 4ـ السيطرة الأمريكية على النفط العالمي. 5ـ النتائج والتوصيات. Oil is considered one of the most important sources of energy for the world in general and American economy in particular, because of the best physical characteristics that it enjoys among other energy sources. Because petrol is superior scientifically and practically to other sources of energy, its importance is clear as main supporter of economy. The USA is one of the largest producers and consumers in the world. So oil is one of the resources that arouse its interest and push it sometimes to use to give promises and sometimes issue threats to guarantee monitoring the world’s oil reservoirs and means of transportation. Taking all that into consideration the research tackled the following points to serve the subject: 1-The American economy. 2-The Importance of oil for the American economy. 3- The reasons behind the decrease of the American reservoirs. 4-The American control of world oil. 5-Results and recommendations.